SETIA-IMS: A PARTNER-BASED DIGITAL INTERVENTION TO IMPROVE SEXUALLY TRANSMITTED INFECTION SCREENING UPTAKE AMONG PREGNANT WOMEN IN RURAL BALI - Putu Indah Sintya Dewi; Ni Made Dwi Yunica Astriani; Cindy Meilinda Sari; Aditha Angga Pratama (Jambura Journal of Health Sciences and Research, 2026)
Sexually transmitted infection (STI) screening is an essential component of antenatal care to prevent pregnancy complications and vertical transmission. However, screening coverage among pregnant women in rural areas, including Buleleng Regency, remains suboptimal, partly due to limited partner involvement. This study introduces SETIA-IMS (Suami Terlibat Aktif–IMS; Actively Involved Husband for STI Prevention), a partner-based intervention integrating a narrative-based educational mini series, digital reminders, couple counseling, and mutual commitment to improve STI screening uptake among pregnant women. This study aimed to evaluate the effectiveness of the SETIA-IMS intervention in increasing STI screening coverage in rural areas. A quasi-experimental study with a pretest–posttest control group design was conducted among 80 pregnant women in rural Buleleng Regency. The intervention group received the SETIA-IMS program for two weeks, while the control group received standard antenatal care. Data were analyzed using the chi-square test and paired t-test with a significance level of 0.05. STI screening coverage in the intervention group increased from 32.5% to 75.0%, whereas the control group increased from 30.0% to 42.5%, with a significant difference between groups (P-value=0.001; OR=4.50; 95%CI: 1.80–11.25). Knowledge and partner involvement also improved significantly in the intervention group (P-value0.001). The SETIA-IMS intervention was effective in increasing STI screening coverage through strengthened partner involvement supported by digital and narrative-based educational strategies. This intervention has the potential to be integrated into antenatal care services to improve maternal health outcomes in rural settings.